Environmental attitudes on Setiu Wetlands, Malaysia - Hassan, Suziana; Olsen, Soren B.; Mohammad Afandi, Syamsul Herman; Thorsen, Bo J. (e-International Publishing House, 2018)
This study addresses the attitudes of the urban and rural dwellers towards Setiu Wetlands conservation. The New Ecological Paradigm (NEP) scale is adopted to measure the degree of environmental concern. A series of factor analysis and regression is applied to analyze the urban-rural attitudes and to suggest three factors structure of attitudes to wetland conservation. The urban-rural residential variable is able to predict in part the overall NEP scores and element of anti-anthropocentrism which suggesting the urban communities are more positive towards wetland conservation. Hence, further outreach efforts in rural population are worthwhile to raise conservation awareness.